2021
DOI: 10.1063/5.0049558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airflow pressure on the droplet breakup in the shear breakup regime

Abstract: In this paper, the coupled level set volume of fluid and the large eddy simulation methods are adopted to perform three-dimensional simulations of the shear breakup of a water droplet. We investigate the effect of airflow pressure (1–3 atm) on the temporary deformation and breakup characteristics, including the breakup initiations, the cross-stream, and streamwise deformations. In addition, special attention is paid to subsequent sub-droplet size distributions, which are generally ignored by many researchers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In SIE, the unstable waves develop near the equator, causing the formation of ligaments and fragments at the edges while the frontal area remains smooth (Kékesi, Amberg & Prahl Wittberg 2016; Zhu et al. 2021). The secondary breakup process of non-Newtonian fluids drop has been investigated in many studies.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In SIE, the unstable waves develop near the equator, causing the formation of ligaments and fragments at the edges while the frontal area remains smooth (Kékesi, Amberg & Prahl Wittberg 2016; Zhu et al. 2021). The secondary breakup process of non-Newtonian fluids drop has been investigated in many studies.…”
Section: Introductionmentioning
confidence: 85%
“…The simulation results indicated that the recirculation zone in the air-flow field significantly influences the pressure distribution on the surface of the droplet, leading to the interior shift of liquid in the droplet and the deformation of the droplet. In SIE, the unstable waves develop near the equator, causing the formation of ligaments and fragments at the edges while the frontal area remains smooth (Kékesi, Amberg & Prahl Wittberg 2016;Zhu et al 2021). The secondary breakup process of non-Newtonian fluids drop has been investigated in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…where ∆ represents the largest dimension of the local FV cell, while C DES stands for a calibration coefficient. This way, the flow regions wherein the grid-based length scale ∆ results in it being sufficiently less than the turbulent length scale (10) are assigned the LES-like mode of the solution. In these regions, the amount of turbulence kinetic energy is locally reduced, which leads to lowering the modeled turbulent eddy-viscosity below the corresponding RANS level.…”
Section: Detached-eddy Simulationmentioning
confidence: 99%
“…Numerical simulations typically attempt to duplicate laboratory experiments, in order to predict the drift, deformation, and successive breakup of parent droplets, e.g., Ref. [10]. Depending on the actual Reynolds and Mach (Ma) numbers, the physics of the process involves a compressible turbulent two-phase flow field that is characterized by a very wide range of spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation